Peranan Budaya Organisasi, Reward dan Punishment dalam Meningkatkan Kinerja Karyawan di BMT PETA Tambak Beras Jombang - Widyaningsih, Bekti; Maulana, M Adi (Universitas KH. A. Wahab Hasbullah, 2023)
This final assignment discusses the role of organizational culture, rewards and punishment in improving employee performance at BMT PETA Jombang. KSPPS BMT PETA is a sharia-based financial institution with a cooperative legal entity. This research aims to find out whether organizational culture, rewards and punishment play a role in improving performance at BMT Tambak Beras Jombang. This type of research is qualitative, the method used is descriptive. The data collection techniques used are observation, interviews and documentation. Data analysis was carried out using data reduction techniques, data presentation and drawing conclusions. The results of the research show that the role of organizational culture that is implemented can support improving employee performance, while the rewards and punishments that are implemented also show that there is a role of reward and punishment that supports improving employee performance. There are obstacles and obstacles in developing human resources at BMT PETA caused by the company and the individuals themselves.